A Case of Adrenoleucodystrophy: Newer Challenge to Rehabilitation (Bangladesh Medical Journal, 2019)
Adrenoleucodystrophy is a rare, genetic demyelinating disorder. Early onset of disease have rapid progression and worse prognosis. It may be associated with adrenal insufficiency. Not much treatment option as though rehabilitation is mainstream of management till death to reduce disability. We report the case of a 10-year-old boy with progressive weakness of all four limb and speech, swallowing difficulty, whose computerized tomography (CT) and Magnetic resonance imaging (MRI) scans showed unusually florid bilateral abnormalities. MRI showed hyperintensities on parieto-occipital lobe through corpus callosum and some biochemical imbalance on serum. The child was diagnosed as a case of Adrenoleukodystrophy and was presented in a clinical meeting for further managements including medical rehab. As this is a very rare case, it was a challenge to handle such type of patient with a course of combined rehabilitation program and discharged home.Bangladesh Med J. 2019 May; 48 (2): 48-50